STRUCTURAL MODIFICATION, PACKING CONFIGURATION AND MODE OF OPERATION OF CEIBA PENTANDRA AND BENTONITE CLAY FOR RESIDUAL OIL REMOVAL - ,, MUHAMMAD AFZAAL (2014)
The pcrfonnance of Ceiba pcntandra (L.) Gaerln (raw kapok fibers, RKF) and raw bentonite for oil sorption and Palm Oil Mill Eft1uent (POME) treatment was compared with structurally modified kapok (NaOH-treated (SKF) and surfacemodified kapok tiber (SMKF)) and HCl treated bentonite clay. Based on FTIR, kapok wax functional group at 1726 cm· 1 was not detected in SKF rendering higher hydrophilicity. SMKF shows the silica characteristic peak at 473 cm-1 attributable to the deposition of silica particles on the surface. The bands at 1098-1123 cm-1 in SMKF may suggest that the Si-0-Si particles overlap with the C-0 stretching vibration of cellulose in tiber, with reduced OH numbers. The reduction in peak intensity at 473 and 523 cm- 1 upon HCl treatment of bentonite, suggests the cleavage ofSi--0--Al bond layer and Si-0-Mg (Fe) bonds.